Development of charged ion exchange resin-polymer ultrafiltration membranes to reduce organic fouling - Ochoa, Nelio Ariel (2006)
This work deals with the performance of polymeric membranes charged with an ion exchange resin on the ultrafiltration (UF) of an oily suspension. The membranes were prepared by the phase inversion process from polysulfone (PSf) solutions and different percentages of resin. The structural and functional study of membranes was carried out by SEM, dextran rejection, streaming potential (SP), oil content and chemical oxygen demand (COD). The structural study showed that there is an important change of the porous membrane substructures leading to a higher densification when the resin content increases. The results showed that the membrane propensity fouling decreased with increasing resin concentration (1-20 wt.% resin). The best performance-less membrane fouling and better permeate quality-was obtained with the membrane prepared with 20 wt.% resin.